2017
DOI: 10.1111/jfd.12592
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering iron regulation with species‐specific transcriptome patterns in Atlantic and coho salmon during a Caligus rogercresseyi infestation

Abstract: Salmon species cultured in Chile evidence different levels of susceptibility to the sea louse Caligus rogercresseyi. These differences have mainly been associated with specific immune responses. Moreover, iron regulation seems to be an important mechanism to confer immunity during the host infestation. This response called nutritional immunity has been described in bacterial infections, despite that no comprehensive studies involving in marine ectoparasites infestation have been reported. With this aim, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Finally, the gene hepcidin-1 is also correlated with sea lice counts in lice-attachment sites. Hepcidin is a regulator of iron metabolism, which as mentioned in the introduction has been associated with response to C. rogercresseyi ( Valenzuela-Muñoz et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the gene hepcidin-1 is also correlated with sea lice counts in lice-attachment sites. Hepcidin is a regulator of iron metabolism, which as mentioned in the introduction has been associated with response to C. rogercresseyi ( Valenzuela-Muñoz et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, comparative analyses of Atlantic and coho salmon parasitized with C. rogercresseyi showed that despite both showing up-regulation of pro-inflammatory genes, the response was highly specific, characterized in coho by an activation of the TH1 response ( Valenzuela-Muñoz et al, 2016 ). Another study linked iron sequestration and depletion mechanisms to the Atlantic salmon immune response to C. rogercresseyi ( Valenzuela-Muñoz et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…From the transcriptome of Atlantic and Coho salmon infected with C. rogercresseyi , a high number of transcripts associated with iron modulation was observed from a GO enrichment analysis (Valenzuela‐Muñoz et al . ,). Furthermore, Atlantic salmon exhibit a high number of transcripts with functions including ion binding, ferric ion binding and ferrous ion binding, processes that were not observed in Coho salmon after infestation (Valenzuela‐Muñoz et al .…”
Section: Catching the Complexity Of Salmon Louse Interactionsmentioning
confidence: 99%
“…Furthermore, Atlantic salmon exhibit a high number of transcripts with functions including ion binding, ferric ion binding and ferrous ion binding, processes that were not observed in Coho salmon after infestation (Valenzuela‐Muñoz et al . ,). Moreover, RT‐qPCR analysis showed high expression levels of aminolevulinic acid synthase (ALAs) and coproporphyrinogenase , genes involved in the haem biosynthesis process.…”
Section: Catching the Complexity Of Salmon Louse Interactionsmentioning
confidence: 99%
See 1 more Smart Citation